The expression of (in)definiteness and genericity in Spanish and Mandarin Chinese (Orkopata. Revista de Lingüística, Literatura y Arte, 2022)
The present work made a brief approach to a grammatical issue that causes some complexity and confusion to students of Spanish as a foreign language (ELE) whose mother tongue is Mandarin Chinese, the article. To do this, first of all, a comparative study of forms and values ​​of articles in both languages ​​is carried out, because in Mandarin Chinese the term "article" does not exist as such, other elements that fulfill the same function are offered. Secondly, through a survey carried out by more than 100 informants, it is observed that it is indeed difficult for Chinese-speaking learners to use the article in their learning of Spanish to a greater or lesser extent. As a result of the indicated problem, an attempt is made to find out the possible reasons why this difficulty is generated and at the same time some suggestions are proposed to improve the teaching-learning process of the article in Spanish by Chinese-speaking teachers and students of ELE.
Keywords: contrastive grammar; Chinese speakers; article; (in)definiteness; genericity